Carbonate-Selective Chromoionophores - Christoph Behringer; Beatrice Lehmann; Wilhelm Simon (CHIMIA)
Three members of a new class of carbonate-selective ion carriers based on trifluoroacetylazobenzene were synthesized and the influence of carbonate on their UV- spectra has been studied.